2008
DOI: 10.1080/03014460802477939
|View full text |Cite
|
Sign up to set email alerts
|

TNF gene polymorphisms in Graves’ disease: TNF-308 A/G meta-analysis

Abstract: Autoimmune thyroid diseases (AITDs), including Graves' disease (GD) and Hashimoto thyroiditis, are associated with human MHC polymorphisms. The present study analysed two polymorphisms within tumour necrosis factor (TNF) genes (TNF-308 A/G SNP and TNFb (CT)n microsatellite) in a sample of 106 GD patients and 199 controls from the Tunisian population. The present study was designed to investigate genetic association of these polymorphisms (taken separately or considered as a haplotype) with GD development. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…It also stimulates the thyroidal production of other cytokines such as IL-6 and IL-8 [8,9] and disturbs the thyroid epithelial barrier [10]. In the current study, we investigated cytokine levels in serum of patients affected with different thyroid pathologies on the basis of the genetic implication of certain cytokine genes (IL-1 and TNF) in thyroid pathogenesis in the Tunisian population [11,12]. Our aim was to determine whether cytokine concentrations in blood serum could be used to discriminate between the different thyroid disease states.…”
mentioning
confidence: 99%
“…It also stimulates the thyroidal production of other cytokines such as IL-6 and IL-8 [8,9] and disturbs the thyroid epithelial barrier [10]. In the current study, we investigated cytokine levels in serum of patients affected with different thyroid pathologies on the basis of the genetic implication of certain cytokine genes (IL-1 and TNF) in thyroid pathogenesis in the Tunisian population [11,12]. Our aim was to determine whether cytokine concentrations in blood serum could be used to discriminate between the different thyroid disease states.…”
mentioning
confidence: 99%
“…Given that the -308 A/G SNP is highly associated with inflammatory diseases such as atopic dermatitis (Behniafard et al, 2012), Graves' disease (Kammoun-Krichen et al, 2008) and bronchial asthma (Witte et al, 2002), several attempts have been made in the past two decades to assign functional significance to this polymorphism. Results from numerous reporter vector-based transient transfection assays revealed that the -308 A-allele confers higher transcriptional activity on the TNF promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Так, в ряде иссле дований показана ассоциация различных полимор физмов гена TNF α и БГ в различных популяциях [13,14,15,16,17]. В недавнем исследовании был вы явлен TNFb3 TNF 308 G гаплотип, имеющий самую сильную ассоциацию с БГ, по данным современного метаанализа [18].…”
Section: Discussionunclassified
“…Так, медиана объема ЩЖ у па циентов с 1 м гистологическим вариантом соста вила 55,3 [42-64] мл, со 2 м вариантом -32,0 [18,9] мл, с 3 м и смешанным (2 й и 3 й) вариантами регистрировались самые низкие пока затели объема ЩЖ -24,0 [14,2-28,3] мл (p < 0,05). Таким образом, можно предположить, что пролифе ративные процессы в ЩЖ при БГ имеют прогреди ентный тип течения, т.е.…”
Section: результатыunclassified